Role of O6-alkylguanine-DNA alkyltransferase in the resistance of mouse spermatogenic cells to O6-alkylating agents - Thompson, M. J.; Abdul Rahman, Suzanah; Baker, T. G.; Rafferty, J. A; Margison, G. P.; Bibby, M. C (Society for Reproduction and Fertility, 2000)
The O6-alkylguanine-DNA alkyltransferase inactivator O6-benzylguanine was administered to BALB/c mice either alone or before exposure to 1,3-bis(2-chloroethyl)- 1-nitrosourea to study the role of the DNA repair protein O6-alkylguanine-DNA alkyltransferase in the protection of the testis against anti-cancer O6-alkylating agents. Exposure of the mice to 1,3-bis(2-chloroethyl)-1-nitrosourea or O6-benzylguanine alone did not produce any marked testicular toxicity at the times studied. Testicular O6-alkylguanine-DNA alkyltransferase concentrations were assayed between 0 and 240 min after O6-benzylguanine treatment and were shown to be > 95% depleted 15 min after treatment with O6-benzylguanine and remained at > 95% at all the times assayed. Histological examination, the reduction in testicular mass and the induction of spermatogenic cell apoptosis showed that this depletion significantly potentiated 1,3-bis(2-chloroethyl)-1-nitrosourea-induced testicular damage after treatment. Major histological damage was apparent 42 days after treatment, demonstrating that the stem spermatogonia were significantly affected by the combination. These results demonstrate that O6-alkylguanine-DNA alkyltransferase plays a significant role in protecting the spermatogenic cells from damage caused by DNA alkylation and indicate that the observed toxicity may result from damage to stem spermatogonia.